Comparison of Endoaortic Balloon Occlusion and Transthoracic Aortic Clamp for Minimally Invasive Cardiac Surgery: Systematic Review and Meta-analysis - Naito, Noritsugu; Takagi, Hisato (International Journal of Angiology, 2025)
This meta-analysis aimed to compare short-term outcomes in patients undergoing minimally invasive cardiac surgery (MICS) using endoaortic balloon (EAB) and transthoracic aortic clamp (TAC) techniques. A comprehensive search of relevant databases was conducted through July 2024. Pooled results were calculated, and subgroup analyses of studies published during early and late eras were performed. Additionally, a meta-regression analysis based on the year of publication was conducted to assess potential influences on outcomes. The systematic review identified 17 non-randomized studies encompassing a total of 8,253 patients. In terms of intraoperative outcomes, no significant differences were observed in operation duration, aortic cross-clamp time, cardiopulmonary bypass time, or rates of sternotomy conversion and iatrogenic aortic dissection. However, subgroup analysis of early-era studies demonstrated significantly longer operation times in the EAB cohort (p = 0.03). Meta-regression analysis indicated that the standardized mean differences in cardiopulmonary bypass time between the two groups decreased in favor of EAB as publication years progressed (p = 0.01). For postoperative outcomes, no significant differences were found in postoperative stroke rate, the rate of reoperation for bleeding, or length of hospital stay. However, the EAB group had significantly lower rates of postoperative atrial fibrillation (OR = 0.82 [0.70–0.95], p < 0.01) and short-term mortality (OR = 0.60 [0.39–0.92], p = 0.04). This meta-analysis demonstrated that EAB is associated with perioperative outcomes comparable to TAC in select patients. The cumulative experience and evolution of techniques may have contributed to improved outcomes with EAB over time.
Keywords: meta-analysis; perioperative outcomes; postoperative complications; minimally invasive cardiac surgery; aortic cross clamp; endoaortic clamp; cardiopulmonary bypass